Prognostic and predictive biomarkers in neuroendocrine tumours. (May 2017) - Chan, David L.; Clarke, Stephen J.; Diakos, Connie I.; Roach, Paul J.; Bailey, Dale L.; Singh, Simron; Pavlakis, Nick
Abstract: Neuroendocrine tumours are extremely heterogeneous malignancies. Despite marked heterogeneity in clinical course and prognosis, few biomarkers exist to help predict prognosis and guide treatment. Many tumour-based biomarkers (Ki-67, mitotic count, genetic/epigenetic changes and microRNAs) exist, but only Ki-67 and mitotic count have strong evidence to support their routine use. Blood-based markers are easily repeatable, but currently established biomarkers (chromogranin A and urinary 5-HIAA) are difficult to measure accurately in practice. Structural imaging is used routinely via the TNM system. Functional imaging such as 68 Ga-based and FDG PET may become valuable biomarkers with their increasing availability, aided by ongoing quantitative research. Multiple nomograms have been proposed to integrate the above factors, but most have not been prospectively validated and are difficult to use in practice. Further research should aim to establish robust new biomarkers and integrate existing ones to help optimise NET treatment.